ANALYSIS OF GEOMETRY CHANGES TO THE ISOLATION ON THE MICROSTRIP BRANCHLINE COUPLER - Yudi Barnadi; Syahrul Nanda; Reggy Zian; Moh. Iqbal; Yoga Purwana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this research, Microstrip Branch line Coupler based simulation will be carried out with each input and output impedance of 50?. where has a different shape (geometry) but has the same dimensions, one is H shape junction and the other is J shape junction. Coupler is a passive multiport device that each port can be the entry point or exit point of the wave. The material used is Epoxy, and works at a frequency of 3.0 Ghz, and can be applied to the duplexer used in pulse radar antenna systems. First, using the initial parameters from the calculation results there was a shift in the working frequency of the desired VSWR value ? 1.5 and the desired coupling factor of -3 dB. For coupler simulation, CST 2019 software is used. The most influential coupler simulation results are the isolation value for H shape junction S14 = -44.79 dB and J shape junction -52,296 dB. Other parameters J Junction Return loss -30,725 dB, insertion loss -3.5926 dB, Factor coupling -3.42 dB. While the value of vswr is = 1. 036, for the H junction value can be seen in the table.